2022
DOI: 10.3390/agronomy12020241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subsurface Drip Fertigation with Nitrogen on the Yield of Asparagus Grown for the Green Spears on a Light Soil in Central Poland

Abstract: During the growing period of many agricultural and horticultural plants, the use of fertigation usually increases the yield; however, the response to this treatment may depend on the cultivar. The effect of subsurface drip fertigation with nitrogen on the yield of three asparagus (Asparagus officinalis) cultivars grown for green spears in light soil was studied. The multi-year (2011–2017) field experiment was carried out on sandy soil and was arranged in a split-plot design with four replications. The first fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Consequently, the water use efficiency of drip irrigation can be significantly improved under various crop evapotranspiration scenarios [37]. In addition, subsurface irrigation with drip irrigation, combined with fertigation, increased production up to 41% as reported by Rolbiecki et al [38]. Subsurface irrigation is not only known as effective and efficient in water used, but also more environmentally friendly.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, the water use efficiency of drip irrigation can be significantly improved under various crop evapotranspiration scenarios [37]. In addition, subsurface irrigation with drip irrigation, combined with fertigation, increased production up to 41% as reported by Rolbiecki et al [38]. Subsurface irrigation is not only known as effective and efficient in water used, but also more environmentally friendly.…”
Section: Discussionmentioning
confidence: 90%
“…The daily evaporated water was recorded every morning (around 7.00 a.m.). For the leaching process, all treatments were supplied with more water ranging from 2 to 4 L/plant six times at 26,33,38,41,46, and 51 days after transplanting (DAT). In addition, this watering was also performed to avoid extreme drought in the growing media.…”
Section: Experimental Design Of the Pocket Fertigationmentioning
confidence: 99%
“…Currently, particular emphasis is placed on water-saving irrigation techniques, including drip irrigation, which, following principles, allows for rational management of this extremely valuable natural resource, water [85][86][87][88][89]. Efforts to reduce the amount of water used to irrigate asparagus are particularly important in water-deficient areas and on light and sandy soils [24,31,36,37,69,71,80,84]. It was found that it is possible to reduce the amount of water used to irrigate asparagus thanks to an appropriate system monitoring this process [72,76,79,80,82,83].…”
Section: Resultsmentioning
confidence: 99%
“…A good solution is a drip irrigation system that delivers water directly to the plant root system and reduces water loss due to evaporation from the soil surface [23,24,[32][33][34]. This irrigation system ensures a high-quality yield of asparagus spears as well [23][24][25]35,36]. Asparagus plants are relatively resistant to a water deficit during summer stem growth.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of subsurface drip irrigation is less employment of hydric resources, provides more consistence of soil water and the nutrient environment which leads to crop growth optimization [76]. Moreover, subsurface drip irrigation has a better yield performance than overground drip irrigation due to efficient water usage [79]. The disadvantages are related to some external impacts affecting the irrigation system being the most important climate affectations, soil type and crop cultivation [76].…”
Section: Sub-surface Drip Irrigationmentioning
confidence: 99%